Retraction Note to: Upregulation of INF-γ, IL-6, and IL-8 expression during replication of turkey coronavirus in nonepithelial cells obtained from Meleagris gallopavo - Cristina Cardoso, Tereza [UNESP]; Colin Panegossi, Letícia [UNESP]; Gameiro, Roberto (Springer Nature, 2022)
The Editor-in-Chief has retracted this article because the image in the bottom right-hand panel of Figure 1a appears to overlap with the image in the top far-right-hand panel of Figure 4 shown at a different magnification in an article [1] reporting a study in a different species. The Editor-in- Chief therefore no longer has confidence in the data presented. The corresponding author Tereza Cristina Cardosa has stated on behalf of all co-authors that they do not agree with this retraction.
Retraction Note to: Upregulation of INF-γ, IL-6, and IL-8 expression during replication of turkey coronavirus in nonepithelial cells obtained from Meleagris gallopavo, (Arch Virol, (2021), 166, (2285–2289), 10.1007/s00705-021-05120-z)